Accidental Injuries in Preschoolers: Are We Missing an Opportunity for Early Assessment and Intervention?. (19th May 2021) - Allan, Carla C; DeShazer, Madeline; Staggs, Vincent S; Nadler, Cy; Crawford, Trista Perez; Moody, Simone; Chacko, Anil
Abstract: Objective: Children with attention-deficit/hyperactivity disorder (ADHD) are at risk for accidental injuries, but little is known about age-related changes in early childhood. We predicted that ADHD would be associated with greater frequency and volume of accidental injuries. We explored associations between ADHD and injury types and examined age-related changes within the preschool period. Methods: Retrospective chart review data of 21, 520 preschool children with accidental injury visits within a large pediatric hospital network were examined. We compared children with ADHD ( n = 524) and without ADHD ( n = 20, 996) on number of injury visits by age, total number of injury visits, injury volume, and injury type. Results: Children with ADHD averaged fewer injury visits at age 3 and 90% more visits at age 6. Children with ADHD had injury visits in more years during the 3–6 age. There were no differences in injury volumes. Among patients with an injury visit at age 3, children with ADHD had 6 times the probability of a subsequent visit at age 6. At age 3, children with ADHD were estimated to have 50% fewer injury visits than children without ADHD, but by age 6, children with ADHD had an estimated 74% more injury visits than children without ADHD. Risk for several injury types for children with ADHD exceeded that for patients without ADHD by at least 50%. Conclusions: Early identification and treatment of preschool ADHD following accidental injury may prevent subsequent injuries. Clinical implications and future directions are discussed with emphasis on the maintenance of parental monitoring into the older preschool years.